Quo Vadis Pendidikan di Masa Pandemi: Menyoal Tanggung Jawab Negara terhadap Hak atas Pendidikan Peserta Didik: Quo Vadis Education in a Pandemic Period: Questioning the State's Responsibility for the Right to Education of Students - Huda, Muhammad Wahyu Saiful; Hidayat, Arif (Seminar Nasional Hukum Universitas Negeri Semarang, 2021)
The covid-19 pandemic affected various aspects of life, one of which was education. Education is one of the most basic human rights that humans have. In the constitution chapter 28 c verse (1), chapter 28 e verse (1) and chapter 31 the constitution of the republic of Indonesia of 1945 have clearly guaranteed the right of education for Indonesian people. Thus, governments are required to implement what is embodied in the constitution during the pandemic. This paper aims to examine the role of governments toward responsibility for the constitutional rights of education during the pandemic. The study was conducted using a juridicum-normative-research method. As a result, Indonesia's education rate declined because of lack of understanding and lack of access to state-provided facilities. This has caused a variety of controversy. On the part of the learner, there are difficulties and pressures on the assignments given by the teacher. It was concluded that the government in this case did not meet the constitution to satisfy the right to pandemic education. Governments are not quick to deal with this issue. But to build a country with adequate human resources and compete internationally, education is a major factor.